2003
DOI: 10.1136/bmj.326.7395.901
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of screening to prevent cancer: analysis of cumulative incidence of cervical abnormality and modelling of cases and deaths prevented

Abstract: Objective To determine the frequency of different outcomes in women participating in cervical screening. Design Analysis of screening records from 348 419 women, and modelling of cases of cervical cancer and deaths with and without screening. Setting Cervical screening programme in Bristol. Results For every 10 000 women screened from 1976 to 1996, 1564 had abnormal cytology, 818 were investigated, and 543 had abnormal histology. One hundred and seventy six had persistent abnormality for two years or more. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(74 citation statements)
references
References 18 publications
2
66
0
6
Order By: Relevance
“…High NPVs could be used to rule out further testing. Is an NPV of 97.4% for CIN3 in women over 40, in whom most CIN will not progress, 3 high enough? The possible value of a negative HPV test in women aged 40 or more in enabling cytology test intervals to be extended should be investigated.…”
Section: Potential Role Of Hpv Testing: Implications Of Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High NPVs could be used to rule out further testing. Is an NPV of 97.4% for CIN3 in women over 40, in whom most CIN will not progress, 3 high enough? The possible value of a negative HPV test in women aged 40 or more in enabling cytology test intervals to be extended should be investigated.…”
Section: Potential Role Of Hpv Testing: Implications Of Our Resultsmentioning
confidence: 99%
“…There are substantial cost implications for the women concerned, and for the health services. 3 There has been controversy about the most effective and efficient management of the large numbers of women who have minor cytological abnormalities. 4 The main methods proposed are cytological surveillance or referral for colposcopy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in 2008, only 54% of adults aged 50 years or older were screened for colorectal cancer. In contrast, 75% of women were screened that year for breast cancer and 72% were screened for cervical cancer (Oxentenko et al, 2007;Nelson and Thorson, 2009;Smith et al, 2010). Recent decades have witnessed the mortality reduction in breast and cervical cancers, largely attributed to the screening programs (Blanks et al, 2000;Raffle et al, 2003), and screening for colorectal cancer is emerging (Benson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…53 The sojourn time with screen-detectable HPV infection and CIN is on average 15-20 years on average before invasive cancer. 34,54,55 Because histologic diagnosis of CIN2-3 may vary 5,56 and since most CIN 2-3 lesions will never progress to invasive cancer, 8,57 the majority of women diagnosed with CIN2-3 will have unnecessary treatment. The number of diagnostic procedures, over-treatments and follow-up examinations is reduced by extending screening intervals, resulting in cost savings without changes in the clinical outcome, as found both by us and others.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Several studies have evaluated the economic impact of cervical screening with and without HPV testing, but have reported variable results. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Possible reasons for discrepancies include different modeling methodologies, use of surrogate endpoints and use of input data based on clinical studies that may not have been representative of the population as a whole. However, most modeling studies have consistently found similar reductions of the cumulative lifetime risk of invasive cervical cancer as a result of cytology and HPV DNA screening.…”
mentioning
confidence: 99%